Pengetahuan, Sikap Dan Motivasi Kader Sebagai Determinan Penemuan Suspek Tuberkulosis Paru Di Wilayah Kerja Puskesmas Karang Mekar Kota Banjarmasin - Agatha Kusuma Wardani; Asrinawaty Asrinawaty; Norfai Norfai (HB PRESS, 2020)
Tuberculosis is an infectious disease that has increased from year to year, This is due to the difficulty of finding a new suspected positive BTA in patients with pulmonary TB or called as Case detection rate (CDR). Alternative tuberculosis programs to increase Case detection rate (CDR) with active case finding involving health cadres. The purpose of the study was to determine and analyze the relationship of knowledge, attitudes and motivation of cadres as a determinant of the discovery of suspected pulmonary tuberculosis in the working area of ​​the Karang Mekar Public Health Center Banjarmasin in 2019. The design of the study used an analytical survey with a cross-sectional approach. The population were all pulmonary tuberkulosis cadres in the Karang Mekar Public Health Center Banjarmasin, which were numbered 48 cadres. The sample used a total sampling technique. The data analysis used chi-square statistical test with 95% of confidence level.Most cadres at the Karang Mekar Public Health Center had good knowledge those were 19 (39.6%), had positive attitudes those were 32 (66.7%), and low motivation those were 31 (64.6%). There was a relationship between cadres' knowledge (p-value = 0.019 ≤ 0.05), motivation (p-value = 0.04 ≤ 0.05) for the discovery of suspected pulmonary TB in the working area of ​​the Karang Mekar Public Health Center Banjarmasin. There was no relationship between attitudes towards the discovery of suspected pulmonary TB in the working area of ​​the Karang Mekar Public Health Center in Banjarmasin (p-value = 0.473> 0.05). The advice needed is improving cadres' understanding further by holding training and providing cadres' motivation by giving awards to cadres who have done their tasks well.